The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cancers14174202
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Mediterranean Diet Intervention on Cancer-Related Fatigue for Patients Undergoing Chemotherapy: A Pilot Randomized Controlled Trial

Abstract: Cancer-related fatigue is a common, burdensome symptom of cancer and a side-effect of chemotherapy. While a Mediterranean Diet (MedDiet) promotes energy metabolism and overall health, its effects on cancer-related fatigue remain unknown. In a randomized controlled trial, we evaluated a rigorous MedDiet intervention for feasibility and safety as well as preliminary effects on cancer-related fatigue and metabolism compared to usual care. Participants had stage I–III cancer and at least six weeks of chemotherapy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 70 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…This effect was more profound for those patients having lower MedDietScores at baseline [40]. The favorable effects of the MD on CRF have been linked with substantial improvements in mitochondrial function including basal respiration, maximal respiration, and spare capacity [40]. It has been documented that obesity in BC is directly linked with CRF, and this association is probably attributed to the high levels of circulating inflammatory cytokines, i.e., tumor necrosis factor-alpha (TNF-alpha) and interleukin-6 (IL-6), as well as blood fatty acid imbalance [41].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This effect was more profound for those patients having lower MedDietScores at baseline [40]. The favorable effects of the MD on CRF have been linked with substantial improvements in mitochondrial function including basal respiration, maximal respiration, and spare capacity [40]. It has been documented that obesity in BC is directly linked with CRF, and this association is probably attributed to the high levels of circulating inflammatory cytokines, i.e., tumor necrosis factor-alpha (TNF-alpha) and interleukin-6 (IL-6), as well as blood fatty acid imbalance [41].…”
Section: Discussionmentioning
confidence: 92%
“…According to the results of a recent randomized trial, cancer patients following the MD for 8 weeks showed a significant amelioration in fatigue, as indicated by FACIT-F scores. This effect was more profound for those patients having lower MedDietScores at baseline [40]. The favorable effects of the MD on CRF have been linked with substantial improvements in mitochondrial function including basal respiration, maximal respiration, and spare capacity [40].…”
Section: Discussionmentioning
confidence: 99%
“… Primary outcome: Nutrition status Intent: Weight maintenance to meet EER. Kleckner et al 2022 [ 30 ] (United States) 33 (2-M, 31-F), Breast cancer, other cancers (23-int, 10-con) Treatment: Chemotherapy Intervention timing in relation to treatment: Undergoing chemotherapy. Details of other treatment NR.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of cancer related fatigue, adoption of the Mediterranean diet was associated with a small-moderate decrease in fatigue levels [44]. High protein [45], carnitine [46,47], Omega-3 [48], American Ginseng [49], Wisconsin Ginseng [50] and Astralagus membranacus [51] reduced fatigue [52].…”
Section: Fatiguementioning
confidence: 99%